2012
DOI: 10.1080/15524256.2011.652857
|View full text |Cite
|
Sign up to set email alerts
|

Using a LISTSERV™ to Develop a Community of Practice in End-of-Life, Hospice, and Palliative Care Social Work

Abstract: An e-mail discussion group (SW-PALL-EOL) connects the growing number of social workers interested in palliative and end-of-life care. The article discusses the concept of a technology supported "Community of Practice." Using content analysis, the article shows empirically how this electronic discussion group has contributed to the growth and expansion of a Community of Practice dedicated to improving palliative and end-of-life care among social workers. Examples are provided of the topics posted by subscribers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
16
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 19 publications
0
16
0
Order By: Relevance
“…8, 29 Murty and others 7 suggested that new members remain observers on a listserv for a period of time, until they feel comfortable posting. The authors of one study who explored online listening behaviours equated noncontributors with listeners in face-to-face conversations; they concluded that listening is a distinct and important part of participation in online discussions.…”
Section: -28mentioning
confidence: 99%
See 4 more Smart Citations
“…8, 29 Murty and others 7 suggested that new members remain observers on a listserv for a period of time, until they feel comfortable posting. The authors of one study who explored online listening behaviours equated noncontributors with listeners in face-to-face conversations; they concluded that listening is a distinct and important part of participation in online discussions.…”
Section: -28mentioning
confidence: 99%
“…[4][5][6] Although listservs are increasingly used to share knowledge in many professional networks, little has been published about how pharmacists use them. [7][8][9][10][11] Listserv communication has been used in different ways within the health care system, including caregiver support, peer support for individuals with various diseases, and as an information-sharing tool for health care professionals. [8][9][10]12,13 The latter have used listservs for networking, for sharing resources, and for accessing the expert opinions of colleagues.…”
mentioning
confidence: 99%
See 3 more Smart Citations